A computing method‐based rearrangement of network protocols to improvise quality factors of FACTS devices and sensors using Newton‐Raphson technique. (7th February 2020) - Sundaravazhuthi, V.; Alli Rani, A.; Manoj Kumar, M.
Abstract: The load flow analysis project was carried out using the Newton‐Raphson's iteration technique and a multiobjective method was suggested to minimize power loss, increase bus voltage, reduce operating costs, and controlling the flexible AC transmission system (FACTS) controllers. The key focus is to improvise the load sustainability subjected to controlling of system safety, integrity, and stability margins within specified limits by acquiring optimum place, installation expenses for FACTS controllers. It is important to analyze the benefits and architect the FACTS devices for the power steady state analysis. For effective modeling, the five bus standard is analyzed without the FACTS end devices and with the FACTS controllers. Transient voltage is critical which requires accurate and quick response to avoid the voltage collapse and instability issues. The Newton‐Raphson's method of load flow analysis is an iterative method which approximates the set of nonlinear simultaneous load flow equations to a set of linear simultaneous load flow equations using Taylor's series expansion and the terms are limited to first order approximation. The variations in voltage are within 5% for a well designated power system. If it exceeds the specified limit then the performance of equipment will be poor and the life of equipment will reduce. Hence the voltage control is very important to improvise the quality factor of the FACTS controllers and devices in power system. The voltage variations in a bus or node are related to reactive power. If the reactive power is injected to a bus is less than reactive power drawn from the FACTS devices, the voltage instability becomes infinite issue causes damage to the controllers and devices. In a load flow problem, two quantities are specified for each bus and the remaining quantities are obtained by the load flow equation analysis using Newton‐Raphson method. This method has been tested for IEEE 30 bus system and then the values are compared and analyzed with MATLAB.